SISTEM PENDUKUNG KEPUTUSAN DALAM PEMILIHAN PENGEMBANGAN MODEL PEMBELAJARAN DENGAN METODE AHP - Zulfi Azhar; Wakhinuddin Wakhinuddin; Waskito Waskito (STMIK Royal, 2021)
Abstract: Education as an important aspect, in improving the quality of education needs to be done innovatively. Learning Models are examples of student learning patterns or structures that are designed, implemented, and systematically evaluated by teachers in order to achieve learning objectives. The Industrial Revolution 4.0 currently has an influence in various fields, one of which is the world of education, with IoT presenting an industrial revolution in the world of education in finding ways to implement learning systems so that they are not outdated. STMIK Royal is one of the computer high schools in Kisaran that wants to develop a better learning model for its students. In choosing the development of learning models requires a decision support system method in choosing the best using the AHP method. This method can analyze a number of criteria and alternatives in choosing the best learning model development which is determined through the calculation process. This model is easier and more effective to produce the best. The AHP method is able to produce the selection of learning model development with several selection criteria and influential alternative choices. The result of the highest ranking is a priority on criteria and alternatives in achieving the goal of choosing a learning model at STMIK Royal Kisaran. Keywords: alternative; analytical hierarchy process; criteria, development; learning models Abstrak: Pendidikan sebagai aspek penting, dalam peningkatan mutu pendidikan perlu dilakukan secara inovatif. Model Pembelajaran adalah contoh pola atau struktur belajar siswa yang dirancang, dilaksanakan, dan dievaluasi secara sistematis oleh guru dalam rangka mencapai tujuan pembelajaran. Revolusi Industri 4.0 saat ini telah memberikan pengaruh di berbagai bidang salah satunya dunia pendidikan, dengan IoT menghadirkan revolusi industri di dunia pendidikan dalam mencari jalan mengimplementasikan sistem pembelajaran agar tidak ketinggalan zaman. STMIK Royal merupakan salah satu sekolah tinggi komputer di Kisaran yang ingin mengembangkan model pembelajaran yang lebih baik bagi mahasiswanya. Dalam memilih pengembangan model pembelajaran memerlukan metode sistem pendukung keputusan dalam memilih yang terbaik menggunakan metode AHP. Metode ini dapat menganalisis sejumlah kriteria dan alternatif dalam memilih pengembangan model pembelajaran terbaik yang ditentukan melalui proses perhitungan. Model ini lebih mudah dan efektif untuk menghasilkan yang terbaik. Metode AHP mampu menghasilkan pemilihan pengembangan model pembelajaran dengan beberapa kriteria seleksi dan alternatif pilihan yang berpengaruh. Hasil perangkingan tertinggi merupakan prioritas pada kriteria dan alternatif dalam pencapaian tujuan memilih model pembelajaran di STMIK Royal Kisaran. Kata kunci: alternatif; analytical hierarchy process; kriteria; pengembangan; model pembelajaran